Biocompatibility of calcium phosphate bone cement with optimized mechanical properties. Issue 2 (12th March 2015) - Palmer, Iwan; Nelson, John; Schatton, Wolfgang; Dunne, Nicholas J.; Buchanan, Fraser J.; Clarke, Susan A.
Abstract: The broad aim of this work was to investigate and optimize the properties of calcium phosphate bone cements (CPCs) for use in vertebroplasty to achieve effective primary fixation of spinal fractures. The incorporation of collagen, both bovine and from a marine sponge ( Chondrosia reniformis ), into a CPC was investigated. The biological properties of the CPC and collagen–CPC composites were assessed in vitro through the use of human bone marrow stromal cells. Cytotoxicity, proliferation, and osteoblastic differentiation were evaluated using lactate dehydrogenase, PicoGreen, and alkaline phosphatase activity assays, respectively. The addition of both types of collagen resulted in an increase in cytotoxicity, albeit not to a clinically relevant level. Cellular proliferation after 1, 7, and 14 days was unchanged. The osteogenic potential of the CPC was reduced through the addition of bovine collagen but remained unchanged in the case of the marine collagen. These findings, coupled with previous work showing that incorporation of marine collagen in this way can improve the physical properties of CPCs, suggest that such a composite may offer an alternative to CPCs in applications where low setting times and higher mechanical stability are important. © 2015 The Authors. Journal of Biomedical Materials Research Part B: Applied Biomaterials Published by Wiley Periodicals, Inc. 104B:308–315, 2015.